Revisiting impact in the context of workplace research: a review and possible directions. Issue 2 (4th December 2017) - Wall, Tony; Bellamy, Lawrence; Evans, Victoria; Hopkins, Sandra
Abstract : Purpose: The purpose of this paper is to revisit the scholarly impact agenda in the context of work-based and workplace research, and to propose new directions for research and practice. Design/methodology/approach: This paper combines a contemporary literature review with case vignettes and reflections from practice to develop more nuanced understandings, and highlights future directions for making sense of impact in the context of work-based learning research approaches. Findings: This paper argues that three dimensions to making sense of impact need to be more nuanced in relation to workplace research: interactional elements of workplace research processes have the potential for discursive pathways to impact, presence (and perhaps non-action) can act as a pathway to impact, and the narrative nature of time means that there is instability in making sense of impact over time. Research limitations/implications: The paper proposes a number of implications for practitioner-researchers, universities/research organisations, and focusses on three key areas: the amplification of research ethics in workplace research, the need for axiological shifts towards sustainability and the need to explicate axiological orientation in research. Originality/value: This paper offers a contemporary review of the international impact debate in the specific context of work-based and workplace research approaches.